The Influence of the Covid-19 Pandemic on the Professional Identities of Health Care Workers - Shushentha Naidoo; Shaun Denvor Ruggunan (SAGE Open)
The professional identity of health care workers is in constant reconstruction. Since identity is fluid, it is easily influenced and the Covid-19 pandemic created change which affected the professional identity of health care workers. Based on structuration and positioning theories, the purpose of this paper is to answer the question: how has the Covid-19 pandemic influenced the professional identity of health care workers? The methodology applied was qualitative. Six individuals participated in 60-min semi-structured interviews. Three themes emerged from this study. These themes are; professional strain and identity management, crisis and reconstruction and experiences of Covid-19. The study found that through the challenges of Covid-19, the professional identity of health care workers was strained. To support the professional identities of health care workers, it is recommended that policies on creating and promoting identities need to be guided.